Nutrient loading on subsoils from on-site wastewater effluent, comparing septic tank and secondary treatment systems - MISSTEAR, BRUCE DUDLEY; O'LUANAIGH, NIALL; JOHNSTON, PAUL MEREDITH; GILL, LAURENCE WILLIAM (My University, 2009)
The performance of six separate percolation areas was intensively monitored to ascertain the attenuation effects of unsaturated subsoils with respect to on-site wastewater effluent: three sites receiving septic tank effluent, the other three sites receiving secondary treated effluent. The development of a biomat across the percolation areas receiving secondary treated effluent was restricted on these sites compared to those sites receiving septic tank effluent and this created significant differences in terms of the potential nitrogen loading to groundwater. The average nitrogen loading per capita at 1.0 m depth of unsaturated subsoil equated to 3.9 g total-N/d for the sites receiving secondary treated effluent, compared to 2.1 g total-N/d for the sites receiving septic tank effluent. Relatively high nitrogen loading was, however, found on the septic tank sites discharging effluent into highly permeable subsoil that counteracted any significant denitrification. Phosphorus removal was generally very good on all of the sites although a clear relationship to the soil mineralogy was determined.
PUBLISHED
Keywords: Nitrogen; Phosphorus; On-site wastewater; Septic tank; Percolation; Subsoil